Depressive disorder among the end-stage renal disease patients undergoing maintenance hemodialysis at Chitwan medical college (Journal of Psychiatrists' Association of Nepal, 2023)
Background: Patients with End stage renal disease (ESRD) suffer from a variety of losses, including renal function, family role, work role, sexual function, as well as time and mobility, all of which have a substantial influence on their lives. Physical manifestation of the End-Stage Renal Disease patients receiving dialysis treatment may be obvious but studies have found that they are also at increased risk of clinical and subclinical Depressive Disorder for a variety of reasons; which might be overlooked in our routine clinical assessment. Depressive Disorder has been associated with impaired recovery and increased mortality in many diseases including End-Stage Renal Disease patients.Objectives: To assess the magnitude of depressive disorder among the patients undergoing hemodialysis of duration >3 months at Chitwan Medical College Teaching Hospital (CMCTH) and to determine the association between explanatory variables with depressive disorder.Methods: Patients undergoing maintenance hemodialysis at CMCTH after meeting inclusion criteria were enrolled by consecutive sampling technique. Diagnoses were assessed on the basis of the ICD-10 Classification of Mental and Behavioral Disorders- Diagnostic Criteria for Research (ICD-10 DCR). To stratify the severity of the Depression into mild, moderate and severe categories, we used Hamilton Depressive Disorder rating scale. Seventy-four (74) patients undergoing maintenance hemodialysis were assessed. Interviews with patients and informants were taken and filled in a self-designed demographic datasheet. Obtained data were analyzed by using descriptive and inferential statistics.Results: The prevalence of the depressive disorder among patients undergoing maintenance hemodialysis was 75.70%. Positive correlations were found between depressive disorder and gender, age group and occupation(p